Understanding Physicians' Perceptions of Overuse of Health Services in Oncology. (October 2021) - Ellen, Moriah; Perlman, Saritte; Horowitz, Einav; Shach, Ruth; Catane, Raphael
Overuse rates in oncology are high, but areas of possible improvement exist for reducing it and improving quality of care. This study explores perceptions and experiences of oncologists in Israel regarding overuse of health services within oncology. In-depth, semistructured interviews were conducted focusing on causes of overuse, facilitators for reduction, and suggestions for improvement. Interviews were audio recorded, transcribed, coded, and thematically analyzed. Physicians reported patient-level causes including "well-informed" and "demanding" patients; physician-level causes including desire to satisfy patients, lack of confidence, time, and skills; and system-level causes like ease of access, and lack of alignment and coordination. Physicians can reduce overuse through patient dialogue, building trust and solidifying patient–physician relationships, and further reduce overuse with better teamwork. Improvements can be made through educational initiatives, and bottom-up solutions. Policy makers and decision makers should develop appropriate interventions addressing health service overuse, including improving patient education and instilling confidence and knowledge in physicians.